EMPLOYMENT ELASTICITY OF OUTPUT IN THE CONSUMER GOODS MANUFACTURING SECTOR OF INDIA DURING THE POST-LIBERALIZATION PERIOD - Batra, Bhavnit Singh; Singh, Atvir (International Journal of Research -GRANTHAALAYAH, 2025)
This paper estimates the employment elasticity of output for India’s consumer-goods manufacturing sector using industry-level data for 1991–92 to 2019–20. While prior research has examined elasticity at the aggregate or all-manufacturing level, no study has evaluated the KLEMS-defined consumer-goods sector as a distinct analytical unit or assessed how capital deepening conditions its employment responsiveness. Using fixed-effects regressions across constituent industries, the analysis reports sector-level elasticities for the full period and two post-liberalization sub-periods, with and without controls for capital intensity. The results show that sector-level elasticity is close to zero over the long run and turns negative in the 2003–04 to 2019–20 sub-period, indicating labour-displacing growth. Controlling for capital intensity raises elasticity somewhat but does not reverse this pattern. Industry-level estimates reveal pronounced heterogeneity: Wood Products and Textiles exhibit consistently negative elasticities, while Pulp and Paper and manufacturing n.e.c. display modest employment absorption. These findings align with the labour-productivity framework proposed by Kapsos (2005) and indicate that rising capital–labour ratios and sector-specific structural characteristics have progressively reduced the employment content of growth in consumer-goods manufacturing.